CAPITAL CITY OF NUSANTARA (IKN): POSITIVE OR NEGATIVE SIGNAL? - Muhammad Daffa Martiza Prasetyo; Herlinda Maya Kumalasari; Ika Oktaviyanti (Antis Publisher, 2025)
Objective: The development of Indonesia’s new capital city (IKN) in East Kalimantan presents significant implications for companies involved in the project, especially those listed on the Indonesia Stock Exchange (IDX). This study aims to examine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and trading volume on stock prices of contractor companies engaged in the IKN project. Method: A quantitative method using multiple linear regression was employed on secondary data from six selected companies during Q1 2022–Q3 2024. Results: The results indicate that ROA has a significant positive effect, DER has a significant negative effect, while trading volume has no significant effect on stock prices. Novelty: These findings highlight that profitability and capital structure are key determinants of stock price movements in the context of national-scale infrastructure projects.